Historical problems in the relations between the PRC and the countries of East Asia - K. A. Sanin (Сравнительная политика, 2015)
Historical problems nowadays have become one of the major factors of international relations. It is also the case for East Asia. In China, there has been an ancient tradition of applying history for the needs of modernity, in order to resolve the objectives of domestic and foreign policy. The analysis of the PRC’s position on historical problems with its neighbors demonstrates that the Chinese leadership pragmatically uses historical problems in order to achieve China’s state interests in the region.